2001
DOI: 10.1002/1096-911x(20010101)36:1<213::aid-mpo1052>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Minimal residual disease at the time of peripheral blood stem cell harvest in patients with advanced neuroblastoma

Abstract: Therefore, the presence of TH mRNA in PBSCs appeared to be associated with an unfavourable outcome, although this was not statistically significant. In summary, RT-PCR for TH mRNA is a sensitive method for the identification of tumour cells in PBSC harvest. The presence of TH mRNA in PBSC harvest may reflect disease status and be associated with an unfavourable outcome, although long-term clinical outcome studies in a larger patient cohort are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 28 publications
2
16
1
Order By: Relevance
“…The presence of TH mRNA was detected in 50% of PBSC obtained from 18 NB patients using RT-PCR and seemed to be associated with an unfavorable outcome, although these results were not significant. 6 In a cohort of 27 NB patients, Corrias et al 10 identified TH in 41% of PBSC using RQ-PCR but did not find any correlation between PBSC contamination and patient survival. In another work, these authors analyzed, using the RT-PCR method, 69 samples obtained from 38 patients and maintained that patient survival was not affected by PBSC contamination.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The presence of TH mRNA was detected in 50% of PBSC obtained from 18 NB patients using RT-PCR and seemed to be associated with an unfavorable outcome, although these results were not significant. 6 In a cohort of 27 NB patients, Corrias et al 10 identified TH in 41% of PBSC using RQ-PCR but did not find any correlation between PBSC contamination and patient survival. In another work, these authors analyzed, using the RT-PCR method, 69 samples obtained from 38 patients and maintained that patient survival was not affected by PBSC contamination.…”
Section: Discussionmentioning
confidence: 97%
“…9 The presence of TH messenger ribonucleic acid (mRNA) in PBSC obtained from 18 patients seemed to be associated with an unfavorable outcome, even though it was not significant. 6 This finding is not supported by Corrias et al 10 who found that patient survival is not affected by PBSC contamination.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…By comparison, TH was detected in 44 of 47 tumors (94%), a similar rate to that previously described in the literature. [25][26][27] Initial tests performed with serial dilutions of a reference tumoral cDNA showed that a detection of this marker expression is possible in dilutions of at least five orders of magnitude (1/100,000); therefore, the real-time RT-PCR may be considered as a highly sensitive technique. This high-sensitivity technique allows the detection of low tumoral infiltration rates, which is a very important aspect to monitor the patient response after the different treatment steps.…”
Section: Discussionmentioning
confidence: 99%
“…Immunomagnetic CD34 ϩ cell selection (ICS) is a new technology that may be employed to deplete the graft from the autoreactive T cell clones in some selected autoimmune diseases, to reduce tumor cell contamination in specific autotransplant protocols, or to diminish the T cell load to modulate the graft versus host disease/graft versus leukemia (GVHD/GVL) reactions in the allotransplant setting with a reduced intensity conditioning regimen (4)(5)(6)(7). At the moment, HLA haploidentical transplantation is the field in which ICS is usually used to obtain both a high dose of purified CD34 ϩ cells together with efficient T and B cell depletion to overcome the bone marrow barrier and to minimize the risks of GVHD and Epstein-Barr virus (EBV)-related lymphoma (8,9).…”
Section: Introduction I Mmunoselected Peripheral Blood Stem Cellsmentioning
confidence: 99%